Gene–Dose Effect of MEFV Gain-of-Function Mutations Determines ex vivo Neutrophil Activation in Familial Mediterranean Fever - Stoler, Iris; Freytag, Judith; Orak, Banu; Unterwalder, Nadine; Henning, Stephan; Heim, Katrin; von Bernuth, Horst; Krüger, Renate; Winkler, Stefan; Eschenhagen, Patience; Seipelt, Eva; Mall, Marcus A.; et al. (Frontiers in Immunology, 2020)
Familial Mediterranean Fever (FMF) is caused by mutations within the Mediterranean Fever (MEFV) gene. Disease severity depends on genotype and gene dose with most serious clinical courses observed in patients with M694V homozygosity. Neutrophils are thought to play an important role in the initiation and perpetuation of inflammatory processes in FMF, but little is known about the specific characteristics of these cells in FMF patients. To further characterize neutrophilic inflammatory responses in FMF and to delineate gene-dose effects on a cellular level, we analyzed cytokine production and activation levels of isolated neutrophils derived from patients and subjects with distinct MEFV genotypes, as well as healthy and disease controls. Serum levels of Interleukin-18 (IL-18) (median 11485 pg/ml), S100A12 (median 9726 ng/ml) and caspase-1 (median 394 pg/ml) were significantly increased in patients with homozygous M694V mutations. Spontaneous release of S100A12, caspase-1, proteinase 3, and myeloperoxidase (MPO) was restricted to ex vivo cultured neutrophils derived from patients with two pathogenic MEFV mutations. IL-18 secretion was highest in patients with two mutations, but also increased in neutrophils from healthy heterozygous MEFV mutation carriers, exhibiting an ex vivo gene-dose effect, that was formerly described by us in patient´s serum. CD62L (L-selectin) was spontaneously shed from the surface of ex vivo cultured neutrophils (median of geometric mean fluorescence intensity (gMFI) after 5 hours 28.8% of the initial level). While neutrophils derived from healthy heterozygous mutation carriers again showed a gene-dose effect (median gMFI 67.1%), healthy and disease controls had significant lower shedding rates (median gMFI 83.6% and 82.9%, respectively). Co-culture with colchicine and/or stimulation with ATP and LPS led to a significant increase in receptor shedding. Neutrophils were not prevented from spontaneous shedding by blocking IL-1 or the NLRP3 inflammasome. In summary, the data demonstrate that ex vivo cultured neutrophils derived from FMF patients display a unique phenotype with spontaneous release of high amounts of IL-18, S100A12, MPO, caspase-1 and proteinase 3 and spontaneous activation as demonstrated by the loss of CD62L. Neutrophilic activation seems to be independent from IL-1 activation and displays a gene-dose effect, that may be responsible for genotype-dependent phenotypes.